Decoding Hegemony in Digital Marketing Jobs: A Semantic Network Analysis of Jobstreet Indonesia - Nurimansyah, Rafi; Dwi Arianto, Irwan (Pusat Pengembangan Kebijakan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2025)
The rapid growth of Indonesia’s digital workforce has been accompanied by increasingly symbolic dynamics in the labor market, especially in how language shapes perceptions of job value. This study analyzes how employers use language in job advertisements to construct symbolic hierarchies and maintain dominance, particularly in the digital marketing sector. Using a descriptive quantitative approach and semantic network analysis, 987 job listings containing the keyword “digital marketing” were collected from Jobstreet over a one-month period and analyzed through bipartite (job title–requirement) and monopartite (job title–job title) networks. The results show that English-dominant job vacancies are closely associated with senior-labeled positions and higher salary offers, while Indonesian appears more frequently in operational roles with lower pay. However, symbolic elevation through titles such as “Manager” or “Specialist” often fails to correspond with actual compensation, and positions requiring many skills are frequently framed with low-status labels such as “Intern” or “Remote,” indicating the use of language to normalize job status while obscuring workload imbalances. Salary information is also often undisclosed, limiting bargaining power and weakening transparency. Additional descriptive findings indicate a geographical concentration of high-value jobs in Jakarta, where English proficiency is more frequently required and median wages are notably higher. Overall, this study demonstrates how recruitment language operates as a form of linguistic hegemony—normalizing inequality by framing structurally similar jobs as symbolically distinct—and highlights the need for stronger regulation and public awareness regarding fair compensation and transparent hiring practices in Indonesia’s digital labor market.